2014
DOI: 10.1007/s11113-014-9343-8
|View full text |Cite
|
Sign up to set email alerts
|

Bucking the Trend: Is Ethnoracial Diversity Declining in American Communities?

Abstract: Although increasing diversity at the national scale is a well-documented trend, substantial variation in patterns of ethnoracial change occurs across American communities. Our research considers one theoretically implied path: that some communities are ‘bucking the trend’, becoming more homogeneous over time. Using 1980 through 2010 decennial census data, we calculate panethnic (five-group) entropy index scores to measure the magnitude of diversity for nearly 11,000 census-defined places. Our results indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 39 publications
0
16
0
Order By: Relevance
“…Our evidence on counties along the Rio Grande and the lower Mississippi River hints that the potential for diversity decline should also be examined more fully (see Lee and Hughes 2015). Consider the future of a high-diversity county with approximately equal proportions of whites, blacks, Hispanics, and Asians.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Our evidence on counties along the Rio Grande and the lower Mississippi River hints that the potential for diversity decline should also be examined more fully (see Lee and Hughes 2015). Consider the future of a high-diversity county with approximately equal proportions of whites, blacks, Hispanics, and Asians.…”
Section: Resultsmentioning
confidence: 87%
“…Many communities are experiencing an increase in ethnoracial diversity, but they differ markedly in initial composition and subsequent group-specific growth rates (Hall et al 2016). For some places, the ascendance of one group to numerical majority status has actually produced a diversity decline (Lee & Hughes 2015). …”
mentioning
confidence: 99%
“…In 2000 and 2010, persons reporting two or more races are assigned to the Other category as well. Although these multirace persons constitute a very small share of the total population, previous research indicated that their inclusion as Other produces a slightly higher than expected rise in diversity between 1990 and 2000 (Lee and Hughes 2015). A sensitivity analysis that omitted the Other category, including those reporting two or more races, did not change any of our substantive findings.…”
Section: Methodsmentioning
confidence: 92%
“…After that point, ethnoracial transition is expected to accelerate, with the ascendant group filling most vacancies, other groups departing (or at least increasing less rapidly), and the composition of the neighborhood turning more homogeneous. Lee and Hughes (2015) documented this kind of transition at the place level, showing that ethnoracial diversity declines between 1980 and 2010, although rare, were more common in places with high diversity levels at the beginning of the period.…”
Section: Introductionmentioning
confidence: 95%
“…Because the addition of the multirace option has more than doubled the size of the still-small ‘other’ category in most states (with Hawaii experiencing the biggest gain), diversity receives a minor boost between 1990 and 2000 but overall patterns (trend lines, differences among states, etc.) are minimally affected (see Lee and Hughes 2015). …”
Section: Data and Measuresmentioning
confidence: 99%